Spatial heterogeneity evolution and driving mechanism analysis of land use change in major river basins: a case study of urban agglomerations in the Yellow River Basin - Hua Wang; Haolin Xu; Xuefei Hong; Cunjin Wang; Jiqiang Niu; Chaoqin Zhang (Geocarto International)
Exploring the dynamics of land resource distribution within major river basins is pivotal for informing ecological conservation efforts and fostering sustainable development. The Yellow River Basin is a crucial region for human activities and economic development in China. This study meticulously examines the evolution of land use patterns across the seven principal urban agglomerations within the Yellow River Basin from 1990 to 2020. Employing the Multiscale Geographically Weighted Regression (MGWR) model, the research rigorously scrutinizes the multi-scale spatial heterogeneity of cultivated land dynamics within urban agglomerations during the years 2010 and 2020. The results show pronounced disparities in land utilization among urban agglomerations, with upstream areas predominantly characterized by grass and downstream regions dominated by cultivated land. Noteworthy is the significant expansion of construction land, particularly manifesting dynamic shifts over time. Furthermore, the driving mechanisms exhibit discernible scale variations, with evident spatial heterogeneity in their impact on cultivated land changes.